Accidental and late parasitological diagnosis of Leishmania sp. in a dog from a low disease transmission area of Brazil: a case report - Spinelli, Renan M.; Uchôa, Flávia F.M.; Menezes, Rodrigo C.; Santos, Fernanda N.; Sudré, Adriana P. (Austral Journal of Veterinary Sciences, 2019)
Canine Leishmaniasis diagnosis must be fast and accurate since dogs are urban reservoirs of the disease and earlier therapeutic intervention is more clinically effective. However, this still represents a challenge, particularly in low transmission areas. The present report describes the difficulties of clinical suspicion and the late diagnosis of a dog infected with Leishmania sp.